Safety of nalmefene for the treatment of alcohol use disorder: an update - López-Pelayo, Hugo; Zuluaga, Paola; Caballeria, Elsa; Brink, Wim Van den; Mann, Karl; Gual, Antoni (Expert opinion on drug safety, 2020)
Introduction: Reduced drinking has been debated as a treatment goal for heavy drinking alcohol-dependent patients, in whom treatment based on abstinence is not always an option. Nalmefene was the first drug approved by the European Medicines Agency (2013) with the indication of reduced drinking in high drinking risk level alcohol-dependent patients. Six years after its introduction in Europe, data from clinical experience can be compared with those from preclinical studies and pivotal registration studies to evaluate what nalmefene has added to the treatment of AUD.Areas covered: Systematic review of efficacy and safety data of nalmefene use in humans from preclinical, phase III and phase IV studies, including systematic reviews, meta-analyses, cost-effectiveness analyses, and other secondary analyses.Expert opinion: Nalmefene introduces a paradigm change in the treatment of AUD that makes it appealing to patients that are reluctant to embrace abstinence, and facilitate patient-centered care in heavy users. However, information regarding safety data in special populations (e.g., patients with alcohol-related diseases, pregnancy, psychiatric disease), and direct comparisons with other potential drugs for alcohol reduction are further needed. Despite the promising role of nalmefene, there are still some factors that limit its wide prescription further than in specialized settings.